Sublimation as a paradigm of the psyche constitution: Metapsychology and theoretical-clinical developments - Tavares, Leandro Anselmo Todesqui; Hashimoto, Francisco [UNESP] (FapUNIFESP (SciELO), 2016)
The present study aims at understanding sublimation as a psychic event inextricably linked to the advent of the subject, being then characterized as a singular and paradigmatic subjectivation process in what regards the psychic constitution. We begin with a brief theoretical-conceptual review with respect to Freud's process of sublimation, as well as the return and deepening carried out by Lacan, and considering contemporary articulations on the subject, we relate its importance, long neglected, with regard to the aspects and theoretical-clinical developments, as well as its fundamental importance with respect to understanding the psychic constitution within the psychoanalytic framework.
Keywords: Creative processes; Psychoanalysis; Sublimation